2010
DOI: 10.1108/03090561011047490
|View full text |Cite
|
Sign up to set email alerts
|

A new understanding of satisfaction model in e‐re‐purchase situation

Abstract: PurposeThe purpose of this paper is to investigate the satisfaction consequences in repurchase situations.Design/methodology/approachOnline travel services are chosen because customers in these types of services had direct contact with firms. A conceptual model of CS‐RPI link is developed and used to test proposed hypotheses. A total of 514 respondents are used to test the proposed model.FindingsThe empirical findings indicate that psychological mediators are useful when repurchase situations are considered. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0
26

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 90 publications
(100 reference statements)
10
79
0
26
Order By: Relevance
“…The findings of the in-depth interviews and the online experiment highlighted the overlapping features of each of the variables. Previous studies (Khalifa;Liu, 2007;Song;Zinkhan, 2008;Novak, 2009;Ha et al, 2010;Rose et al, 2012) have outlined that numerous variables are capable of influencing the customer experience, however this study extends the current body of literature by introducing a new higher order variable and asserting the equal importance of each of these variables together influencing the customer's experience, proving hypothesis H1(a-e). The findings of this research show that the combined variable of 'website characteristics' has a direct and indirect effect on the customer experience through the length of time spent on the website, requiring to seek customer support and through the success of the search.…”
Section: Theoretical Contributionssupporting
confidence: 53%
See 1 more Smart Citation
“…The findings of the in-depth interviews and the online experiment highlighted the overlapping features of each of the variables. Previous studies (Khalifa;Liu, 2007;Song;Zinkhan, 2008;Novak, 2009;Ha et al, 2010;Rose et al, 2012) have outlined that numerous variables are capable of influencing the customer experience, however this study extends the current body of literature by introducing a new higher order variable and asserting the equal importance of each of these variables together influencing the customer's experience, proving hypothesis H1(a-e). The findings of this research show that the combined variable of 'website characteristics' has a direct and indirect effect on the customer experience through the length of time spent on the website, requiring to seek customer support and through the success of the search.…”
Section: Theoretical Contributionssupporting
confidence: 53%
“…The first contribution is the introduction of exploring the online customer experience within a utilitarian context of online business support. Past research has explored the customer experience in relation to the online shopping environment (Ha et al, 2010;Khalifa;Liu, 2007;Novak, 2009) and investigating outcomes of repurchase intention (Rose et al, 2012). This paper has provided theoretical insight into a utilitarian search for online information during the customer's journey to finding information.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Bansal et al (2004) found website characteristics, the specific website's value, and its relative value as important drivers of website satisfaction. Ha et al (2010) highlighted the role of positive attitude in the formation of a customer-satisfaction and repurchase intention. There is a significant relationship between website quality and user satisfaction, and this relationship affects the actual use of online services (Li and Jiao 2008, Gounaris et al 2010, Udo et al 2010.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…In such matter, there is a study stated that fashion, preferences, style, purchasing behavior and the view the social group can influence the consumer to be committed to use e-retailing or not (Liao & Shi, 2009). On top of that, a research also mentioned that the higher the positive experiences gained by the consumer, the higher the chances of expectations in future purchases (Ha, Janda & Muthaly, 2010). The mission of Amazon.com has always "to be Earth`s most customercentric company" , to provide positive experiences by having many products available on sale, conveniently with a reasonable price (Amazon.com, 2014).…”
Section: Expectationmentioning
confidence: 99%